UNUSED PRINTED-MASS MEDIA FOR TEACHING ENGLISH IN DIFFERENT TYPES OF SKILLS - Dini Puspita Wati (EDUCAFL : Journal of Education of English as Foreign Language, 2018)
Abstract:  As language teachers, being creative  has become a need to help students to achieve their best performance. This paper is intended to describe how to use the unused printed mass media, such as magazines and newspaper for teaching English to become more fun and  enjoyable. Thus, the paper  focuses on how the teacher can make use of the unsued printed mass—media and develop teaching materials from them. The paper also discusses the  learning stages in  using the unused magazine or newspaper. News paper and magazines are considered as authentic   as they can be easily found in everyday life. Using the unused printed mass-media in the  language classroom  has many advantages because they are  cheap,  easy to get, fun, and  environmentally friendly.Key words: Learning stages,  unused-printed mass media,  taching English.